PHC-026 Tacrolimus and Imatinib Interaction. A Case Study. (12th March 2013) - Selvi-Sabater, P; Rizo-Cerda, AM; Arribas-Diaz, B; Morego-Soler, A; Bosó-Ribelles, A; Sánchez-Mulero, MC; Sánchez-Martinez, I; Manresa-Ramón, N; Espuny Miro, A; Castilla-Llorente, C
Abstract : Background: Tacrolimus is a drug metabolised by CYP3A4. Since imatinib increases the plasma concentrations of simvastatin, a CYP3A4 substrate, this indicates that it is an inhibitor of this enzyme and may affect other drugs. Purpose: To describe the possible interaction between imatinib and tacrolimus that result in increased blood levels of Tacrolimus. Materials and Methods: Information was collected through the SAVAC and SELENE computer systems and reviewing patient history. The variables compiled were tacrolimus blood levels, dose and dose regimen. Results: The patient had an allogeneic blood stem cells transplant from an unrelated donor, HLA and ABO compatible, presenting cutaneous sclerodermiform graft versus host disease (GVHD) on tacrolimus (2 mg/12 h) treatment and blood levels around 4 ng/ml for 12 weeks. After starting treatment with imatinib, in the following five tests tacrolimus levels ranged from 5.8 ng/ml to 8.9 ng/ml with no change in the dose of tacrolimus. After 45 days of treatment imatinib was suspended and tacrolimus levels recorded in the following test after discontinuation of imatinib fell to around 4 ng/ml. Conclusions: The increase in tacrolimus blood levels, without changing the dose, supports the possible interaction between imatinib and tacrolimus. No conflict of interest.